Reactive astrocytes undergo M1 microglia/macrohpages-induced necroptosis in spinal cord injury. Issue 1 (December 2016) - Fan, Hong; Zhang, Kun; Shan, Lequn; Kuang, Fang; Chen, Kun; Zhu, Keqing; Ma, Heng; Ju, Gong; Wang, Ya-Zhou
Abstract Background A unique feature of the pathological change after spinal cord injury (SCI) is the progressive enlargement of lesion area, which usually results in cavity formation and is accompanied by reactive astrogliosis and chronic inflammation. Reactive astrocytes line the spinal cavity, walling off the lesion core from the normal spinal tissue, and are thought to play multiple important roles in SCI. The contribution of cell death, particularly the apoptosis of neurons and oligodendrocytes during the process of cavitation has been extensively studied. However, how reactive astrocytes are eliminated following SCI remains largely unclear. Results By immunohistochemistry, in vivo propidium iodide (PI)-labeling and electron microscopic examination, here we reported that in mice, reactive astrocytes died by receptor-interacting protein 3 and mixed lineage kinase domain-like protein (RIP3/MLKL) mediated necroptosis, rather than apoptosis or autophagy. Inhibiting receptor-interacting protein 1 (RIP1) or depleting RIP3 not only significantly attenuated astrocyte death but also rescued the neurotrophic function of astrocytes. The astrocytic expression of necroptotic markers followed the polarization of M1 microglia/macrophages after SCI. Depleting M1 microglia/macrophages or transplantation of M1 macrophages could significantly reduce or increase the necroptosis of astrocytes. Further, the inflammatory responsive genes Toll-like receptor 4 (TLR4) and myeloid differentiation primary response gene 88 (MyD88) are induced in necroptotic astrocytes.In vitro antagonizing MyD88 in astrocytes could significantly alleviate the M1 microglia/macrophages-induced cell death. Finally, our data showed that in human, necroptotic markers and TLR4/MyD88 were co-expressed in astrocytes of injured, but not normal spinal cord. Conclusion Taken together, these results reveal that after SCI, reactive astrocytes undergo M1 microglia/macrophages-induced necroptosis, partially through TLR/MyD88 signaling, and suggest that inhibiting astrocytic necroptosis may be beneficial for preventing secondary SCI.